Analisis Kedisiplinan Siswa Sekolah Dasar Kelas IV di SDN 5 Raja Pangkalan Bun - Heri Romansyah; Holten Sion; Nyoto Nyoto (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2026)
Discipline is one of the important aspects in shaping students’ character in elementary school. This study aims to analyze the level of discipline among fourth-grade students and to identify the factors that support and hinder the implementation of discipline at SDN 5 Raja Pangkalan Bun, West Kotawaringin Regency. The study employed a descriptive qualitative approach supported by simple quantitative data. Data collection techniques included observation, interviews, questionnaires, and documentation. The research subjects consisted of 24 fourth-grade students, the homeroom teacher, and the principal. The results showed that the students’ level of discipline was in the high category, with an average questionnaire score of 3.38 and an observation result of 3.43. The highest discipline indicator was found in students’ polite behavior toward teachers, while the lowest indicator was found in students who still played during the learning process. Supporting factors for discipline included teachers’ role modeling, the consistent implementation of school rules, and the habituation of a positive school culture. Meanwhile, inhibiting factors included limited parental supervision at home, the geographical conditions of students’ residences, and peer influence. This study emphasizes the importance of collaboration between schools and parents in fostering students’ disciplined character in a sustainable manner.